ANATOMICAL VARIATIONS OF THE AORTIC ARCH - Zivadinovik, Julija; Matveeva, Niki; Zafirova, Biljana; Dodevski, Ace; Petrovska, Tanja (Journal of Morphological Sciences; Vol 1 No 1 (2018): JMS, 2018)
Anatomical variations of the aortic arch and its branches can have important implications on prognosis and management of surgical interventions, as well as on radiological diagnostics and interventional radiology. The presence and the pattern of arch variants may increase the technical difficulty of surgical procedures, thus detailed evaluation of aortic arch anatomy is important for planning thoracic surgery and endovascular interventions. The aim of this study was to present the anatomical variations of the aortic arch and its branches in a large group of patients using CTA and consequently to obtain data on their representation in our population. The study population included 550 patients with referral diagnoses requiring CTA chest radiography, which visualizes the aortic arch. The anatomic features of the aortic arch itself and supra-aortic vessels were analyzed, and anatomical variations were recorded on each CT image. The results showed that 91.3% of the patients had the usual pattern of the aortic arch, 8.7% had variations in the number of the supra-aortic vessels. The most common variation of the number of the aortic arch branches was their reduction to two, with left common carotid artery arising from brachiocephalic trunk (5.63%). The knowledge of the anatomy of the aortic arch and its branches and identification of arch anomalies allow accurate surgical and intervention planning and helps avoiding potential complications.